Autologous Fat Grafting in the Treatment of Painful Postsurgical Scar of the Oral Mucosa - Andrea Lisa; Valeria Summo; Valeria Bandi; Luca Maione; Matteo Murolo; Francesco Klinger; Marco Klinger (Case Reports in Medicine)
Background. Persistent pain as a consequence of surgical treatment has been reported for several common surgical procedures and represents a clinical problem of great magnitude. Material and Methods. We describe the case of a 47-year-old female who presented a retractile scar that adhered to deep planes at the upper right of the vestibule due to surgical removal of maxillary exostosis, which determined important pain symptoms extending till the right shoulder during both chewing and rest. We subsequently treated her with autologous fat grafting according to Coleman’s technique. Results. Clinical assessments were performed at 5 and 14 days, 1, 3, and 6 months, and 1 year after surgical procedure. We observed a progressive release of scar retraction together with an important improvement of pain symptoms. Conclusion. The case described widens the possible application of autologous fat grafting on a new anatomical site as buccal vestibule and in one specific clinical setting confirming its promising biological effects.